Grassland Management for Climate Change Adaptation and Watershed Protection in Karnali Watershed Area - Pokhrel, Kabi Prasad (Tribhuvan University Journal, 2013)
Karnali watershed area is very sensitive and need of scientific management of highland grasslands which are rich in number of plants and animal species that have significant role and contribution in national economy and ecology. However, these grass lands are in threat and exist in their natural state within protected areas as neighboring grasslands and forest habitats have been rapidly degraded. At higher altitudes, trans-Himalayan and alpine rangelands are home to a diverse array of wildlife and are grazed by livestock, which are an integral part of the livelihood of several different ethnic groups. These grasslands are being overgrazed and little is known about the ecology and sustainability of prevailing land use practices at the community level. In this context, the prime concern of the paper is to address the existing issues, challenges along with biodiversity characteristics of the higher altitude grasslands of the region. Thus, the main focus of the paper is to point out the major issues of grasslands along with location specific as well as innovative measures and devises for the effective management of grassland beyond the protected and adjoin areas. Further, the paper explores some applicable measures to high land grassland management strategies with active participation of local communities with a view to provide comprehensive policy guidance for the sustainable management of grasslands in order to build the capacity of locals on the road to climate change adaptation and watershed protection in the Karnali region.